Dialogue Summary: Creating Community-based Specialty Clinics in Ontario - Moat, KA; Lavis, JN (My University, 2013)
A summary of what was learned from a stakeholder dialogue that addressed problems related to community-based specialty clinics, options for addressing these problems, key implementation considerations, and next steps for creating community-based specialty clinics in Ontario.
Keywords: community; specialty; clinics; Ontario